Multiple criteria analysis of dwelling facilities maintenance/Daugiabučių gyvenamųjų namų priežiūros proceso daugiakriterinė analizė - Malinauskas, Pranas; Petrašsenko, Tatjana (Journal of Civil Engineering and Management, 2001)
Nowadays the maintenance problem of many-flat houses becomes one of the mostly debatable points. Greatly pressing questions are the quality of maintenance work and evaluation of public utilities. In this paper, the process of building maintenance is analyzed, in order to plan and carry out a more effective maintenance process. Striving for this aim the activities of subjects carrying out maintenance work, demands of building users were analyzed in a complex way and the comparison of maintenance variants was made. Striving for prolonging the time of building existence, it is necessary to increase maintenance quality and effectiveness in distributing resources, to improve organisational and management forms, to raise qualification of maintenance executives. The determination of the utility degree and value of the project under investigation and establishment of the priority order for its implementation does not present much difficulty, if the criteria numerical values and significances are obtained and the multiple criteria decision-making methods are used. The results of the comparative analysis of the projects are presented as a decision-making matrix where columns contain n alternative projects being considered, while all qualitative information pertaining to them is found in lines. Qualitative description of the project provides the information about the aspects of a building facility (i e convenience, work quality, health level of environment, noise level, work level, etc). Qualitative information is based on the criteria systems, units of measurement, values and initial significances as well as the data on the alternative projects development. In order to select the best project, it is necessary, having formed the decision-making matrix, to perform the multiple criteria analysis of the projects. One of the major tasks is to determine the significances of the criteria. When performing multiple criteria assessment of projects, it is necessary to normalise the values of criteria describing the projects and then to weigh them. The significances of all criteria must be coordinated among themselves. A method of multiple criteria evaluation of the projects discussed in this paper assumes a direct and proportional dependence of significance and priority of investigated versions on a system of criteria adequately describing the alternatives and on values and significances of the criteria. The system of criteria is determined and experts calculate the values and initial significances of criteria. All this information can be corrected by process participants (customer, users, etc) taking into consideration their pursued goals and existing capabilities. The degree of utility AT of a building life cycle is directly associated with quantitative and conceptual information related to it. A degree of building life cycle reflects the extent to which the goals pursued by the process participants are attained.Article in Lithuanian.First Published Online: 30 Jul 2012